Joint ROM during standing and seated double pole ergometry - Jensen, R. L.; Leissring, S. K.; Tervo, J. L.; Watts, P. B. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Tervo and Jensen (2009) found that stand-up Nordic skiers, using a sit-ski device obtained peak linear velocity at the same point during the poling cycle as a sit-ski athlete. Tervo et al (2010) found that the rectus femoris was highly activated in sit-skiing and more-so than in stand-up skiing. However, no studies have examined differences in shoulder (SH), elbow (EL), and trunk (TR) movement during these two versions of double poling. Thus the purpose of this study was to compare joint range of motion (ROM) while standing and sitting using a double pole ergometer.